Loss of serine/threonine protein phosphatase 6 severely impairs sexual stage development in malaria parasite Plasmodium berghei. - Yonghui Feng; Wenyan Gao; Chengqi Wang; Shuangrui Shi; Dan Zhou; Lin Sun; Liying Zhu; Liwang Cui; Yaming Cao; Xiaotong Zhu (PLoS Pathogens)
Protein phosphorylation plays a critical role during the development of malaria parasites. Here, we performed a functional analysis of the Plasmodium berghei Ser/Thr protein phosphatase 6 (PbPP6), which is associated with the plasma membrane of macrogametes and ookinetes. Compared to wild-type P. berghei, the genetic disruption of pbpp6 (∆pbpp6) resulted in reduced asexual growth of the parasites and prolonged survival of infected mice. The ∆pbpp6 parasites showed impaired gametogenesis, particularly affecting male gametogenesis, which substantially decreased both ookinete formation and mosquito transmission. Transcriptomic analysis revealed an over 11-fold downregulation of nek3, a regulator of MAPK2 within the PKG-Ca2⁺ signaling cascade, foreshadowing pathway dysregulation that was further evidenced by significantly diminished intracellular cGMP levels, decreased cytosolic Ca2⁺ mobilization, and reduced DNA replication in activated Δpbpp6 gametocytes. Phosphoproteomic analysis detected increased phosphorylation at the Ser508 site of guanylyl cyclase alpha (GCα), indicating that PbPP6 regulates cGMP-PKG-Ca2+ signaling through modulation of GCα activity during gametogenesis. Additionally, we observed altered expression of messenger ribonucleoproteins in the Δpbpp6 parasites, which may affect the translational repression of stored mRNAs in female gametocytes and impact post-fertilization development in mosquitoes. Collectively, this study highlights the potential of targeting PP6 to disrupt malaria transmission.